Analysis Of The Influence Of Green Input, Green Process, And Green Product On Economic Performance At PT Herba Emas Wahidatama - Pratiwi, Iramandha Putri; Widayanti, Sri; Syah, Mirza Andrian (Universitas Mercu Buana, 2025)
Objectives: The impact of production on the traditional medicine industry and efforts to preserve environmental and economic performance. Therefore, this study aims to analyze the effects of green inputs, green processes, and green products on the financial performance of PT Herba Emas Wahidatama.Methodology: This study uses a quantitative method. Sampling was carried out using saturated sampling, collecting data from 60 personnel from various departments who are actively involved at PT Herba Emas Wahidatama. The analysis and hypothesis testing techniques used SEM-PLS with the SmartPLS 4.0 program.Finding: The results of this study indicate that the green input carried out by PT Herba Emas Wahidatama has a significant influence on economic performance, as indicated by one of its key indicators, namely raw material control, using the FIFO and FEFO methods. Meanwhile, the processed data on the green process variable applied to PT Herba Emas Wahidatama also has a significant impact on economic performance, as indicated by the efficient energy use indicator in the production process, which utilizes solar panels. The green product variable applied to PT Herba Emas Wahidatama has a significant effect on economic performance, which is indicated by one of the indicators, namely product certification, including product certification from BPOM in the form of CPOTB (Good Traditional Medicine Manufacturing Practices) and CPPOB (Good Processed Food Production Practices), Halal MUI, and several ISO standard certifications starting from its commitment to SMM ISO 9001:2015, SMK3 45001, and SML 14001.Conclusion: The better the implementation of green input, processes, and products, the more sustainable and competitive the economic performance of PT Herba Emas Wahidatama will be in its market.